The Role of Bitcoin Halving in Influencing the Dynamics of Bitcoin Trends in 2012-2025 - Pratama, Rico Aji; Suripto, Suripto; Harori, M. Iqbal (Eastasouth Institute, 2025)
This study aims to analyze the influence of Bitcoin Halving on the dynamics of Bitcoin price trends during the period 2012 to 2025. Using a descriptive quantitative approach, data is obtained through documentation of Bitcoin's historical price from various reliable sources. The sample was determined by purposive sample in the period before and after the halving in 2012, 2016, 2020, and 2024. The analysis was conducted using the Moving Average Convergence Divergence (MACD) indicator to observe trend change patterns. The results show that any halving event is generally followed by a significant upward trend in prices, reflecting an imbalance between demand and supply. Additionally, the MACD has proven to be effective in identifying trend change signals related to halvings. External factors such as regulation and market sentiment also strengthen its impact. This research makes a theoretical contribution to the digital financial literature and practical recommendations for crypto investors.